EVALUATION OF DISEASE SEVERITY ON RICE GENOTYPES TO BACTERIAL BLIGHT USING AMINO ACID CONTENT ANALYSIS (Makara Journal of Science, 2011)
The bacterial blight (BB) disease severity on two rice genotypes i.e.; BP 4110-2d-33 (backcross between Ciherang x Angke; containing Xa-4, xa-5) and BP 3688e-23 (sister lines derived from cingri/memberamo//widas///IRBB 8; containing xa-8) were lower compare with TN-1 (containing Xa-14). The total amino acid content in cultivar’s TN-1 was accounted for about one third to about a half of total amino acid than those of other rice genotypes where the total amino acid was ranging from 1.95% to 4.22%. In BP 3688e-23, and BP 3688e-22 genotypes more amino acid levels were decline although these advance lines showing xa-8 background. BB resistant gene carried by BP 4110-2d-33 and BP 3688e-23 were stable, whilst BP 3688e-22 was less effective to inhibit BB disease severity. Overall, amino acids were not found to be related to the level of BB resistance; where correlation between amino acid content and BB disease severity is not significant. The slower growth of Xoo on rice genotypes BP 4110-2d-33 and BP 3688e-23 may probably due to other than nutritional factors. The degree of resistance in rice genotypes infected by races of pathogen; as well as the resistance gene possessed by genotype BP 3688e-23 need to be further determined.